Growth Inhibition of Colletotrichum gloeosporioides by Trichoderma harzianum, Trichoderma koningii, Bacillus subtilis and Pseudomonas fluorescens - Febrilia Nur ‘Aini; Sri Sukamto; Dwi Wahyuni; Risma Galuh Suhesti; Qurrotun Ayunin (Indonesian Coffee and Cocoa Research Institute, 2013)
Colletotrichum gloeosporioides is a disease which can cause significant yield loss of cocoa. The objective of this research is to investigate the abilityof antagonist microbes, Trichoderma harzianum, Trichoderma koningii, Bacillus subtilis and Pseudomonas fluorescens in controlling gloeosporioides biologically in laboratorium condition. The experiment was carried out in Crop Protection Laboratory, Indonesian Coffee and Cocoa Research Institute. Results of this research showed that antagonist fungi, T. harzianum, T. koningii, had a stronger ability in inhibiting growth of C. gloeosporioides about 83% compared to the ability of antagonist bacteria, B. subtilis and P. fluorescens, only about 49%. Key words: Growth inhibition, Colletotrichum gloeosporioides, Trichoderma harzianum, Trichoderma koningii, Bacillus subtilis, Pseudomonas fluorescens.